Hand Written English Character Recognition using Pattern Sampling Recognition Technique (PSRT) - Mandal, Rakesh Kumar (International Journal of Computer Sciences and Engineering, 2025)
This is the era of intelligent computing devices. Efforts are going on in all over the world to develop machines and programs which can solve the problems that human beings can solve with ease. One such field is recognition of handwritten characters by computers. In this paper the neural network is first trained using perceptron-learning algorithm. The target pattern is a collection of distinct patterns set for each character. While testing the target pattern is sampled and the distortion in the sampled pattern was compared with the original one. 30% or less of such distortion was considered for the identification of a particular character. The results showed that such methods produce accuracies of at least 90% and more for the hand written upper case English alphabets